2005
DOI: 10.1007/s10546-004-1984-4
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Of Sonic Anemometer Observations In Low Wind Speed Conditions

Abstract: When the wind speed decreases below a certain value (1-2 m s À1 ) meandering (low frequency horizontal wind oscillations) starts to prevail. In these conditions it becomes difficult to define a precise mean wind direction and to estimate the airborne dispersion. To study the wind and turbulence characteristics during meandering, two sonic anemometer datasets, containing hourly wind observations, were analysed: the first one, lasting 1 year, was recorded in complex terrain (Graz, Austria) and the second one, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
187
1
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(213 citation statements)
references
References 42 publications
16
187
1
9
Order By: Relevance
“…In general, the horizontal kinetic energy for submeso flow is poorly related to other local parameters such as wind speed and stability, as also found by Anfossi et al (2005) and Vickers and Mahrt (2007). While the kinetic energy may depend on wind speed for a specific scale range and network, no general behaviour could be found.…”
Section: Dependence On Time Scalementioning
confidence: 82%
“…In general, the horizontal kinetic energy for submeso flow is poorly related to other local parameters such as wind speed and stability, as also found by Anfossi et al (2005) and Vickers and Mahrt (2007). While the kinetic energy may depend on wind speed for a specific scale range and network, no general behaviour could be found.…”
Section: Dependence On Time Scalementioning
confidence: 82%
“…not only in urban conditions. We recall that Anfossi et al (2005) observed that there is not a general consensus in the literature on how to define low wind speeds. This definition is based on a limiting wind speed that ranges from 0.5 to 2.0 m s −1 and they suggested 1.5 m s…”
Section: Eulerian Autocorrelation Functionsmentioning
confidence: 97%
“…Anfossi et al [1] and Vickers and Mahrt [21] found that the kinetic energy of the mesoscale motions based on time variation did not depend significantly on wind speed or stability. However, information on time variation cannot be used to infer spatial variation.…”
Section: Dependence On Scale and Ambient Conditionsmentioning
confidence: 98%